Perlindungan Hukum Pekerja Pemegang Saham di PT. Bank Central Asia Tbk - Sidi Alkahfi Setiawan (JURNAL RECHTENS, 2013)
Looking at the existing problems in the business world, (including in the label industry company engaged in the field of banking services) as a symbol of the dominant economic system, became inherently clear, structure and function is an anti-thesis of a law for the protection of workers, both always contradictory, found the gap between das sollen (must) with das sein (reality) and always appeared discrepancy (gap) between the law in the books and law in action. The gap between das sein das sollen and is due to the difference in perspective between the interests and principles of law (protection of workers) and economic interests (corporate profits), while the law requires the fulfillment of the rights of workers to the maximum, on the corporate side, it actually felt as a barrier because it would reduce the profit or gain. Based on the fact that the authors formulate the problem, which then could conclude as the root of the problem concerning the Legal Protection of Shareholders Workers in PT Bank Central Asia Tbk. Therefore, the need for revision of the package of labor legislation, in order to be able to walk up to the expectations of the presence of packet rules existing labor regulations empower Labour / Trade Unions to be able to carry out the purposes and functions well, the fight for workers' welfare.